Effects of Combined Physical Movement Activity and Multifaceted Cognitive Training in Older People with Mild Cognitive Impairment in a Rural Area - Jiranan Griffiths (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Background: Mild Neurocognitive Disorder (mNCD) is a new term for Mild Cognitive Impairment (MCI). It is a transitional stage between normal cognitive functions and dementia. A review showed that 10-15% of those with MCI progressed annually to dementia or a major neurocognitive disorder. Health professionals worldwide try to examine a variety of strategies for prevention. Objectives: The study aimed to investigate the prevalence and risk factors associated with MCI among older people in a rural community in Chiang Mai. It also aimed to investigate the effect of a combination of physical movement activity and multifaceted cognitive training on cognitive function in older people with mNCD. Methods: In the first phase, a cross-sectional study in 482 people who were 60 years old and over was conducted in On Tai, San Kamphaeng, Chiang Mai, Thailand. The assessments were administered by trained occupational therapists using demographic and health characteristics, Mental Status Examination Thai 10, Activities of Daily Living Scale (Thai Barthel ADL Index), 15-item Geriatric Depression Scale (TGDS-15) and the Montreal Cognitive Assessment - Basic (MoCA-B, Thai version). In the second phase, a randomized control trial in 70 mNCD people, according to DSM-5 criteria, was conducted with an intervention group and a control group (n=35 each). The program for the intervention group included 24 sessions, twice a week. The outcome measures were assessed before and after intervention. It included of attention, memory, executive function, Instrumental of Activity of Daily Living (IADL), and Quality of Life (QoL). Results: The prevalence of MCI in older people was 71.4% (344 out of 482) and it increased with age. The mean age of MCI was 68.3 ± 6.82 years and most had an education ≤ 4 years. Risk factors associated with MCI were low education (RR:1.74, 95%CI:1.21 to 2.51) and diabetes mellitus (RR: 1.19, 95% CI:1.04 to1.36). The combined intervention benefited cognitive functions. Attention, Trail Making Test (TMT) - A was significantly improved in the intervention group (p=0.018). There were significant improvements in memory, digit span sequence (DSS) scores (p=0.024), letter verbal fluency (LVF) (p=0.001) and category verbal fluency (CVF) (p=0.004). Comparing between groups, there was a significant difference in LVF (p=0.001) including immediate (p=0.023) and delayed recall (p=0.036). Executive function, block design improved significantly in the intervention group (p=0.029). IADL scores slightly increased in both groups, but there was no significant difference between groups. In quality of life, a significant improvement was found in physical functions (p=0.001), role limitation due to physical problems (p=0.016), general health perception (p=0.018), health change (p=0.001) and in the total score of quality of life (p=0.001). Conclusions: The prevalence of MCI in older Thai people is high in a rural community. The explanation might be associated with old age, a low education and diabetes mellitus. The combined intervention appears to be effective in delaying cognitive impairment in older people. This program could be used for older people who have similar condition or culture. Trials in other communities are also recommended.